Macroeconomic control, political costs and earnings management: Evidence from Chinese listed real estate companies - Donghua Chen; Jieying Li; Shangkun Liang; Guojun Wang (China Journal of Accounting Research, 2011)
Firms in China have faced high political costs during China's economic transition, because they are affected by macroeconomic policies. However, research to date has offered no consistent conclusions on the relationship between political costs and earnings management in China. This study tests whether real estate firms attempt to decrease earnings during periods of macroeconomic control, using variables related to the national real estate market as proxies for political costs. We find that political costs are negatively related to earnings management in listed real estate firms. In addition, we find that non-state-owned enterprises utilized more income-decreasing accruals during this period. Our results are consistent with the political costs hypothesis.
Keywords: G18; G38; E6; 650; Political costs; Earnings management; State-owned enterprises; Non-state-owned enterprises